Early American Literature (JSTOR)
The journal of the Modern Language Association's American Literature Division I, Early American Literature publishes the finest work of scholars examining American literature from its inception through the early national period, about 1830. Founded in 1965, EAL invites work treating Native American traditional expressions, colonial Ibero-American literature from North America, colonial American Francophone writings, Dutch colonial, and German American colonial literature as well as writings in English from British America and the US. Published three times a year, each issue typically includes four or five articles, the same number of book reviews, and a review essay. Occasionally editions of previously unpublished works appear.
Keywords: American Studies